Can Unearned Income Make Us Fitter? Evidence from Lottery Wins - Joan Costa-i-Font; Mario Gyori (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Although lower income is associated with overweight (and obesity), such an association is explained by a number of other confounding effects such as omitted variables (e.g., time preferences) explaining that income effect on overweight. We study the effect of unearned income shocks resulting from a lottery win (windfall income) on both overweight (alongside obesity and body mass index) distribution. We draw upon longitudinal data from the United Kingdom, a country where about half of a population plays the lottery. Our results suggest no evidence of contemporaneous effects of income on overweight, but a significant lagged effect. We find a reduction in overweight 12 months after a lottery win. A 10,000-sterling win reduces overweight by 2-3 percentage points. Furthermore, we document a nonlinear effect up to 36 months after the lottery win, suggesting that small wins increase overweight and large wins reduce it. The effect of a lottery win varies depending on an individual's working hours and educational attainment. A lottery win among low education individuals decreases the risk of overweight.
Keywords: I12; I18; J30; 330; obesity; overweight; income; windfall income; lottery wins; body mass index (BMI)